CULTURAL CREATIVE POTENTIAL OF LESSONS OF MUSIC ART IN SOLVING THE PROBLEM OF FORMATION OF NATIONAL SELF-CONSCIOUSNESS OF ADOLESCENTS - Саленко, В.В.; Брежнєва, С.Б. (SWorldJournal, 2022)
The modern development of the international relations, the aggravation of ethnic contradictions in Ukraine and other social transformations bring to the fore the problem of the national self-consciousness, which puts before the scientists and the pedagogu